Aqua-Vanadyl Ion Interaction with Nafion® Membranes - Vijayakumar, Murugesan; Govind, Niranjan; Li, Bin; Wei, Xiaoliang; Nie, Zimin; Thevuthasan, Suntharampillai; Sprenkle, Vince; Wang, Wei (Frontiers in Energy Research, 2015)
Lack of comprehensive understanding about the interactions between Nafion membrane and battery electrolytes prevents the straightforward tailoring of optimal materials for redox flow battery applications. In this work, we analyzed the interaction between aqua-vanadyl cation and sulfonic sites within the pores of Nafion membranes using combined theoretical and experimental X-ray spectroscopic methods. Molecular level interactions namely solvent share and contact pair mechanisms are discussed based on Vanadium and Sulfur K-edge spectroscopic analysis.